The Concept of Humans as Khalifah and the Strengthening of Self-Management Based on Hadith in Islamic Religious Education Learning - Arif Wahyudi; Suraijiah Suraijiah; Fahmi Riady; Rusdiana Rusdiana (Ar-rayyan: Journal Of Islamic Education, 2026)
This study aims to examine the concept of humans as khalifah and to integrate it with the strengthening of self-management based on hadith in Islamic Religious Education (PAI) learning. The method used is a literature study with a qualitative approach, analyzing various sources related to Qur’anic verses, hadith, and theories of self-management in education. The novelty of this research lies in the conceptual synthesis between leadership values within the concept of khalifah and self-management indicators explicitly derived from hadith, as well as their implementation in the design of PAI learning. In contrast to other studies that tend to discuss these two aspects separately, this research offers an integrative model that connects theological and practical dimensions in character building, the results of the study indicate that hadith values such as discipline, responsibility, self-control, and planning have strong relevance in shaping students’ self-management abilities. The integration of these values with the concept of khalifah in PAI learning can enhance self-awareness, independence, and effective behavioral management skills. Therefore, PAI learning functions not only as a transfer of knowledge but also as a means of strengthening leadership character based on contextual and applicable Islamic values